The right to live well, from the community legal system and its implication in the relocation of the city of Cerro de Pasco, as a result of open-pit mining works - Palacios Cárdenas, Eda Denise (2021)
The article summarizes the study carried out on the importance of understanding living well, so well known by our ancestral peoples, as a way of life with and for nature and how its understanding can cement the planning that allows the relocation of the population of Cerro de Pasco, a city born as a mining town, product of its immense argentiferous veins, and how this natural «miracle» has become its own destruction. For more than a century, people have been writing about the urgency of housing the population in an environment far away from mining operations. However, the existence of laws has not allowed the longed-for dream of living with dignity to become a reality, because it does not matter that the health of all its inhabitants is undermined in the same proportion as the minerals are extracted. Likewise, together with the affectation of the right to health, other rights are affected, such as cultural heritage, environment, development, and peace.